2022
DOI: 10.1007/s40123-022-00546-3
|View full text |Cite
|
Sign up to set email alerts
|

Living Without a Diagnosis: A Patient’s Perspective on Diabetic Macular Ischemia

Abstract: Diabetic macular ischemia (DMI) is a common complication of diabetic retinopathy (DR) that can result in progressive and irreversible vision loss. DMI is associated with damage in the vessels that supply blood to the retina and the enlargement of the foveal avascular zone. Currently, there are no approved treatments specifically for DMI. Furthermore, there is limited published information about the prognosis, prevalence or outcomes of DMI, and there is no consensus regarding diagnostic criteria. It is vital to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 72 publications
(88 reference statements)
0
3
0
Order By: Relevance
“…Although there is currently no treatment specifically for DMI, 7 the implication of the present study could be interpreted as follows: As DMI has been found to contribute to progressive visual loss among some patients with DR despite treatment, 8 considering the intricate relations between DMI and DR, our results might advocate the early detection of DMI among a diabetes population to herald early intervention, such as stricter metabolic control, to mitigate both DMI and DR progression and subsequently arrest progressive VA deterioration. 44…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there is currently no treatment specifically for DMI, 7 the implication of the present study could be interpreted as follows: As DMI has been found to contribute to progressive visual loss among some patients with DR despite treatment, 8 considering the intricate relations between DMI and DR, our results might advocate the early detection of DMI among a diabetes population to herald early intervention, such as stricter metabolic control, to mitigate both DMI and DR progression and subsequently arrest progressive VA deterioration. 44…”
Section: Discussionmentioning
confidence: 99%
“…6 Current reviews hypothesize that the predominant involvement of DMI in different plexus might explain various structure-function tion, such as stricter metabolic control, to mitigate both DMI and DR progression and subsequently arrest progressive VA deterioration. 44…”
Section: Discussionmentioning
confidence: 99%
“…This paper focuses on the perspectives and experiences of a single individual, an example of what might be termed an instrumental case study [ 13 ], whereby a single case is explored in its full complexity in order to provide illustrative insights into a broader issue. Such an approach has previously been used in ophthalmology to illustrate the complex, unique experiences of individuals living with geographic atrophy [ 14 , 15 ] and diabetic macular ischemia [ 16 ]. Analysis of Chanel’s experience of SCR is interwoven with insights derived from the relevant literature on SCD and its ocular manifestations.…”
Section: Introductionmentioning
confidence: 99%